1990
DOI: 10.1007/bf00318681
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and intracellular routing of peroxidase-conjugated immunoglobulin-G by the perfused human placenta

Abstract: Selected lobules of term human placenta were extracorporeally perfused and human immunoglobulin-G complexed to horseradish peroxidase (IgG-HRP) was added to the maternal perfusate. After different durations of perfusion IgG-HRP was visualised by use of diamino-benzidine cytochemistry. Within the first 10 min of perfusion IgG-HRP was found bound to microvilli and coated pits of the syncytiotrophoblast; internalisation into coated vesicles and tubulo-vesicular bodies was also observed. Subsequently, IgG-HRP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Electron microscopy had been used to trace the pathway of horseradish peroxidase conjugate of IgG through the different tissue layers of the human placenta (Leach et al, 1990). The delay of 2 hours between the start of perfusion of the intervillous space with the conjugated IgG and its detection in endothelial cells of the villous capillaries was consistent with the lag time after addition of IgG to the maternal perfusate until it was detected on the fetal side as observed in the study of Malek et al (1995).…”
Section: Syncytiotrophoblast (Stb)mentioning
confidence: 63%
“…Electron microscopy had been used to trace the pathway of horseradish peroxidase conjugate of IgG through the different tissue layers of the human placenta (Leach et al, 1990). The delay of 2 hours between the start of perfusion of the intervillous space with the conjugated IgG and its detection in endothelial cells of the villous capillaries was consistent with the lag time after addition of IgG to the maternal perfusate until it was detected on the fetal side as observed in the study of Malek et al (1995).…”
Section: Syncytiotrophoblast (Stb)mentioning
confidence: 63%
“…The reason for the inconsistencies between these results is not clear at present, but it might be due to the differences in experimental conditions including the culture cells employed. Earlier electron microscopic studies revealed that IgG was observed in coated pits and coated vesicles in the new born rat intestine and the syncytiotrophoblast of human term placenta (Abrahamson and Rodewald 1981;Leach et al 1990). In addition, recently, He et al (2008) showed that a coated vesicle pinching off from a coated pit was involved in the first steps of FcRn-mediated IgG transport in neonatal rat intestine.…”
Section: Discussionmentioning
confidence: 98%
“…In mammals, IgG transfer is achieved through an active transport mechanism, involving a receptor mediated transcytosis of IgG across the syncytiotrophoblast, and a transcellular pathway through the endothelium [148,149]. In teleosts, although the transfer and the mechanism of uptake, transport and proteolysis of different specific serum proteins to eggs during vitellogenesis are already known [149][150][151][152][153][154], the mechanism of IgM uptake and its storage within the eggs is yet to be established.…”
Section: Mode Of Immunoglobulin/antibody Transfermentioning
confidence: 99%